THE POST-PANDEMIC COVID-19: HAS ECONOMIC GROWTH AND INTERNATIONAL TRADE IN TURKEY CHANGED? - Gokhan, Doruk Hosmunt; Og’lu, Ahmet Muaz Yakup (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Turkey back on its feet without triggering a second wave of the pandemic will be a challenge. But unlike some other countries, Turkey’s political and economic weaknesses serve as further hurdles. This combination of a weak economy and an unending spiral of authoritarianism will make a robust recovery from the pandemic even more difficult. Instead, the path to normalization is likely to be marked by growing political instability and debates over the likelihood of early elections. Qualitative research is a type of research that explores and provides deeper insights into real-world problems. Instead of collecting numerical data points or intervening or introducing treatments just like in quantitative research, qualitative research helps generate hypothenar to further investigate and understand quantitative data. Turkey’s post-pandemic economic growth and international trade have been characterized by a robust recovery in certain sectors, supported by strong export performance and government stimulus. However, challenges such as high inflation, currency instability, and geopolitical risks pose significant hurdles to sustained growth.